Simulering och visualisering av manuell och automatiserad montering - Falk, Frida; Tegenmark, Daniel (My University, 2020)
In today's industries, digitalisation, automation and smart factories are the focus. New technologies replace manual work and result in more efficient production. Traditionally, automation has mainly been applied early in production flows and has set requirements on, for example, product volume and product variation. The fourth industrial revolution, also “Industry 4.0”, involves new techniques and methods that enable higher degree of automation in final assembly. The work is a part of a research project and aims to investigate low-cost automation within a subassembly at the final assembly at Volvo Trucks in Tuve, Gothenburg. The subassembly includes assembly of switches for the front shelf in the truck cabin. The need to automate the assembly is mainly linked to ergonomics, as the assembly includes monotonous work and fine motor skills. The work was carried out in collaboration with Volvo Trucks, the SII-Lab (Stena Industry Innovation Laboratory) and the FCC (Fraunhofer-Chalmers Centre). The project consists of simulating the current and future assembly process with the software IPS IMMA (Industrial Path Solutions - Intelligently Moving Manikin), developed by FCC. No physical model or physical tests have been created within the project. Furthermore, no financial aspects for implementing automation have been addressed. The simulation of the current assembly process was used to evaluate the ergonomics of the assembly and showed that the workload is moderately harmful. The second simulation shows how the assembly can be performed with low cost automation.
Keywords: Digitalisation, automation, smart factories, Industry 4.0, final assembly; low cost automation, ergonomics, simulation.